From conflict to co-operation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The manager of Meru Forest Plantation in northern Tanzania describes how the plantation has made agreements with local communities to share responsibilities and benefits. As a result conflicts over livestock grazing have been minimised, corruption over land distribution has been reduced and no forest fires have taken place for three years.